Edukasi Melalui Media Kwartet dalam Peningkatan Pemahaman Mengenai Air Bersih dan Sanitasi kepada Siswa SMAN 1 Pariaman - Azyyati Ridha Alfian; Fea Firdani; Rosya Triana Dinata; Rida Tartila; Fadilah Yuma Zahara; Fri Gadil; Yoga Tri Pambudi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Based on data from the Health Office of Pariaman City in 2020, 1049 cases of diarrhoea were found. One of the causes is influenced by poor sanitation conditions and water quality, so it needs to be a concern for all levels of society, especially the younger generation. They have an essential role as a driving force for good sanitation for society, which is helpful for survival in the future. In order to reduce the number of cases of diarrhoea and other water-borne diseases, education was carried out using two methods for SMAN 1 Pariaman students, namely the lecture and quartet cards. Pre and post-tests were carried out to compare the effectiveness of the two methods. The pre and post-test scores had an average increase of 2.2 points; for the lecture method, the average increased by 0.4 points. The results obtained from both methods show an increase in the knowledge. However, compared with the difference in the increase of average value pre and post-test, the quartet card games were more effective in increasing student knowledge. This media quartet can continue to be used in health promotion.